INTERSENSORIAL WORLDS IN THE SHORT STORIES OF BORA STANKOVIĆ - Snežana M. Milosavljević Milić (Filolog, 2025)
Starting from the current methodological assumptions of sensory and atmospheric poetics, developed within the framework of the so-called "sensual turn" in the humanities, this paper analyses the sensory aspects of the narrative worlds in Bora Stanković’s short stories. The theoretical foundation of the research is based on the concept of atmospheric perception by M. M. Ponty and G. Beme, as a specific type of synesthetic perception that does not limit experience but gives spatiality to each of our senses, as well as the new phenomenological theory of H. Schmitz on half-entities, which, as quasi-objective givens, carry a strong atmospheric potential. Stanković’s poetics of the sensual is also approached from a perspective that emphasises the connection between the sensory dimension of language and thought, and the cultural nature of their discursive representation. In this context, the typology of the five senses (sight, touch, hearing, taste, and smell) is complemented by the concept of somatic sensations and somatic experience as an important link in the triad with aesthetic and somaesthetic experience. The analysis of representative examples from the original texts confirms our assumption about Stanković’s departure from a visually-centred narrative mediation and his opening towards olfactory, haptic, auditory, and gustatory worlds. This research perspective may thus point to modernist traits of Stanković’s work that cannot be fully contained within the existing receptive paradigms of his sensualism, lyrical narration, and pronounced psychologicalism, while emphasising the importance of Bora Stanković for the genesis of fictional sensotopes in 20th-century Serbian literature.